ACCOUNTABILITY OF PERPETRATORS OF EMBEZZLEMENT CRIMES WITH THEIR COLLEAGUES (Study of Decision Number 65/Pid.B/2024/PN.Sbr) - Niken Rahmawati Putri; Asilah Nur Azizah; Tetuko Rie Wicaksono; Stephanie Octa Zyta Puspita (Ann Publisher, 2025)
Abstract Background. Aims. This research aims to identify and analyze the causative factors of embezzlement committed by a colleague, as well as to analyze the criminal responsibility of the perpetrator in Decision Number 65/Pid.B/2024/PN.Sbr. Methods. This research employs a case study method on the aforementioned court decision. Result. The results indicate that several interconnected factors contributed to the embezzlement, including misunderstandings regarding the financial management of salt sales proceeds, the alleged motive of resentment from the victim, the lack of internal control in the company's financial management, and the close relationship and trust between the perpetrator and the victim, leading to less formal financial management practices. The analysis of the court decision shows that the defendant was legally and convincingly proven guilty of embezzlement as regulated in Article 372 of the Indonesian Criminal Code (KUHP). The Panel of Judges sentenced the defendant to one year and ten months of imprisonment, considering the elements of the crime in the article. Conclusion. This decision demonstrates the proportional application of the principles of legal certainty, justice, and expediency in law enforcement against embezzlement in the context of a working relationship. Implementation. Most importantly, regular communication between management and employees should be improved to create an open and trusting work environment. Embezzlement prevention requires a comprehensive approach that involves structural, cultural, and individual aspects within a company.